2007
DOI: 10.1080/01674820701207403
|View full text |Cite
|
Sign up to set email alerts
|

A model for critical review of literature – with vaginismus as an example

Abstract: In this article we present a behavioral model for the critical review of the literature within a certain research field, using vaginismus as an example. We searched the literature for the title word "vaginismus" and analyzed to what extent the articles dealt with the following seven categories: prevention, etiology, maintaining factors, consequences, object of intervention, method of intervention, and method of evaluation. In each category we scrutinized the content of the articles for biological, psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…Besides lacking randomization, many of the nonrandomized treatment studies have other methodological shortcomings (McGuire & Hawton, 2003;Reissing, Binik, & Khalife, 1999;van de Wiel, 1990;Wijma et al, 2007). A definition of vaginismus is often unclear or even absent.…”
Section: Outcome Measures At Follow-upmentioning
confidence: 97%
See 1 more Smart Citation
“…Besides lacking randomization, many of the nonrandomized treatment studies have other methodological shortcomings (McGuire & Hawton, 2003;Reissing, Binik, & Khalife, 1999;van de Wiel, 1990;Wijma et al, 2007). A definition of vaginismus is often unclear or even absent.…”
Section: Outcome Measures At Follow-upmentioning
confidence: 97%
“…In a majority of nonrandomized studies, positive treatment outcome has been defined as the woman's ability to have intercourse, and often success rates greater than 80%, even 100%, at end of therapy or at follow-up (3 -12 months) have been reported (Reissing et al, 1999;Wijma et al, 2007). In our study, the proportion of positive treatment outcome results at follow-up was highly associated with which definition of treatment outcome we chose to use and thus had a range of 75%: from 81% who were able to have intercourse to 6% who could have totally pain-free intercourse and were able to enjoy intercourse.…”
Section: Outcome Measures At Follow-upmentioning
confidence: 98%
“…[12][13][14][15] and on its partial overlap with vaginismus [1,3•, 6,7•]. Recent research has demonstrated persistent problems with the sensitivity and specificity of the differential diagnosis of these two phenomena [1,3•,5••, 6,12,[15][16][17][18][19]. However, as no consensus has been reached in unifying the two entities, they will be kept separate according to the latest classifications [10].…”
Section: Introductionmentioning
confidence: 97%
“…An intense debate is ongoing on the "real" nature of dyspareunia (is it a "sexual" or a "pain" disorder?) [12][13][14][15] and on its partial overlap with vaginismus [1,3•, 6,7•]. Recent research has demonstrated persistent problems with the sensitivity and specificity of the differential diagnosis of these two phenomena [1,3•,5••, 6,12,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation